Efektivitas Metode Bercerita dalam Mengembangkan Kemampuan Bahasa Anak Usia Dini: Studi Kasus di Tk Negeri 2 Pante Ceureumen - Nurhabibah; Iin Faridah; Ummi Habibatul Islamiyah (Cyber Media Indonesia, 2024)
Language development is a fundamental aspect of early childhood education. Language education for preschool children not only facilitates the acquisition of knowledge but also aims to motivate, guide, and enhance their communication skills. One effective approach to achieving these objectives is the storytelling method. This study seeks to evaluate the effectiveness of the storytelling method in improving language development among early childhood learners at TK Negeri 2 Pante Ceureumen. The research employed a Classroom Action Research (CAR) design, involving two teachers and ten children as participants. Data were collected through observations and structured interviews, and subsequently analyzed using descriptive qualitative methods. The study was conducted in two cycles, each comprising the stages of planning, implementation, observation, and reflection. The results demonstrate a significant improvement in children’s language skills following the application of the storytelling method. In the first cycle, most children were categorized as being in the